Consumer Behavior in the Era of Digital Marketing: Trends and Challenges - Haile Gebrselassie; Abebe Bikila; Derartu Tulu (Universitas Kristen Indonesia Toraja, 2024)
Digital marketing has revolutionized how businesses interact with consumers. This paper examines emerging trends in consumer behavior, such as personalization and social media influence, and addresses challenges like data privacy and trust. Recommendations for effective digital marketing strategies are provided.